The Contribution of Lean Approach in Improving Productivity and Promoting Economic Development in Private Sector Enterprises «Case Study» - Elmashharawi, Zaher (The Arab Journal of Administration, 2018)
Lean approach has developed based on a set of principles and practices that promote the concepts of reduce costs, improve productivity and increase profitability. Within this context, this study has been conducted in order to identify the contribution of the application of lean approach (optimal exploitation of the resources of the company, improve the company’s growth rates, improve production quality) in promoting the concept of economic development. The study showed a range of results, including: The application of lean approach lead to lower costs, improve productivity and increase profitability. It contributes to the optimal utilization of available resources for businesses. It enhances the growth rates in those businesses like productivity rates, profitability rates and the level of cost reduction. The application of lean approach contributes in strengthening of economic development, which will be reflected positively on the national economy and increase the rates of growth. The study recommended that businesses need to shift towards the implementation of lean approach to get its benefits. Businesses which intend to apply lean approach need of training and human resources development on lean culture. Scientific departments at universities must paying attention to spreading awareness of lean approach by including it within the courses, seminars and specialized workshops.